Perlindungan Hukum Terhadap Nasabah yang Menderita Kerugian Atas Kelalaian Pihak Bank yang Mengakibatkan Hilangnya Dana Simpanan Nasabah - Ndraha, Krisdian Rizki Havana; Habeahan, Besty (Universitas Pahlawan Tuanku Tambusai, 2025)
This writing aims to explore how the legal protection of customers who suffer losses due to the negligence of the bank which results in the loss of customer deposit funds. Banks as banking institutions have an obligation to provide legal protection to depositors. Legal protection is a right received by deposit customers from banking institutions to guarantee and protect customer rights, provide legal certainty and as a guarantee of protection to minimize losses to deposit customers. normative legal research, normative legal research is a research method that focuses on understanding and deepening of legal norms, laws and regulations and legal issues related to the writing of this internship journal. This research method also uses library data collection methods, where books, laws and regulations, and also supporting literature to maximize the source of writing this internship report. Based on the results of this writing, the Bank in carrying out its authority in collecting funds from the public in the form of customer deposits, often commits a negligence that results in losses to customers. This loss results in a dispute between the depositing customer and the bank. In the settlement process, two ways can be taken, namely non-litigation dispute resolution efforts (outside the court) and dispute resolution efforts through the court.